La utilización de estrategias metodológicas y su incidencia en el desarrollo de destrezas lógico-matemático de niñas y niños de preparatoria, primer grado de educación general básica de la escuela “Luis Urdaneta” del cantón Pindal, provincia de Loja, periodo lectivo 2013- 2014”. Lineamientos alternativos - Rogel Sànchez, Liliana Carolina (2014)
This thesis refers to: USE OF METHODOLOGICAL STRATEGIES AND THEIR IMPACT ON THE DEVELOPMENT OF MATHEMATICAL SKILLS logical HIGH SCHOOL CHILDREN, FIRST DEGREE GENERAL EDUCATION BASIC SCHOOL "LUIS URDANETA" PINDAL CANTON, Loja Province , 2013- 2014 semester. "ALTERNATIVE GUIDELINES. Previously the General Purpose formulated: Establish the importance that reveals the use of Methodological Strategies as a means to develop skills in logical Mathematical children High School First Grade. The methods used were: Scientist, Inductive, Analytical-Synthetic, Descriptive that helped to follow step by step the investigation; techniques applied were: the survey that applied it to the teachers to identify the type using Methodological Strategies and observation guide applied to children in order to assess the development of logical mathematical skills girls and children. Application of the survey it is concluded that: 100% of teachers use types as Educational Material: Human, Materials Tangibles and Intangibles in the daily work